STRATEGI KOMUNIKASI PEMASARAN MENGGUNAKAN BROSUR DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN RUMAH PADA PERUMAHAN SERASI INDAH SELARAS KARAWANG - Tia Fitri Amelia; Firdaus Yuni Dharta; Made Panji Teguh Santoso (Media Bina Ilmiah, 2022)
This study discusses the marketing communication strategy of the Serasi Indah Selaras Housing in Karawang City offering a residence. In this article, we discuss how the communication strategy planning carried out by the beautiful harmonious housing in Karawang on the decision to buy a house. This study aims to determine the communication strategy used by Serasi Indah Housing Karawang in marketing subsidized housing.The research place used by researchers is Serasi Indah Selaras Karawang Housing. This research takes the subject of research, namely Marketing Management, Marketing Supervisor, and home buyers in the beautiful harmonious housing complex, Kerawang, Karawang. Data collection techniques in the study used in-depth interviews and observations and literature studies. In its communication strategy, Serasi Indah Selaras Housing has done its best and marketed its subsidized housing. This study uses Attention, Interest, Desire, Action (AIDA) Theory in which there are components namely Attention, Interest, Desire, and Action. The research method used is a qualitative research method with a qualitative descriptive approach which aims to better explain or describe how Serasi Indah Selaras Karawang housing markets using brochures in making home buying decisions for customers. The results of this study are Attention, Interest, Desire, and Action.